PERLINDUNGAN HUKUM TERHADAP KORBAN PENYEBARAN CYBER BULLYING DENGAN MOTIF BALAS DENDAM (Studi Kasus Putusan Nomor 96/Pid.Sus/2023/PT BTN) - Aris, Danisa; Sitompul, Rina Melati (Universitas Dharmawangsa, 2024)
The ease of use of social media makes it a platform that is often misused by irresponsible people. The rise of cybercrime, such as cyberbullying, is a concern for law enforcement agencies. Cyberbullying is bullying through social media. Cyberbullying is a crime that often occurs, but its impact receives less attention. Many victims of cyberbullying do not understand what protections are available.The problems in this work are the factors that cause cyberbullying crimes, what are the laws and regulations relating to cyberbullying crimes, and how the analysis of the judge's opinion on case number 96/Pid.Sus/2023/PT BTN. This research uses normative research where the sources used are based on library materials and secondary data. Then the analysis is carried out, where the final conclusion is drawn from the results of the analysis collected.The results of this research explain that criminal responsibility for perpetrators of cyber bullying crimes must still be enforced for their actions in accordance with the provisions contained in Article 27 paragraph 1 (one) of Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 concerning Information and Transactions Electronic.